“Sou uma alma da belle époque”: a família carioca na visão emblemática de Nelson Rodrigues - 1916-1962 - Santos, Leandro Antônio dos (2020)
The doctoral thesis presented here aims to diagnose Nelson Rodrigues' stylistic and historical conception (1916-1962) about Rio de Janeiro, during the period when he took up residence in the city. A wide capacity of the writer to discover the reality to which he was inserted, both in the theatrical and journalistic fields, reveals spaces that transmitted impressions about life; as well as to highlight Nelson Rodrigues' experience as a producer of written culture in Rio de Janeiro and to mobilize the thematic axis of the carioca family immersed in the transformation of the city space. The research seeks to anchor its theoretical framework in the indicative paradigm of Carlo Ginzburg that seeks to decipher reality from the details, signs, evidence and the emblematic vision of a given social reality. This means that the gaze is turned to the common, the banal, and the everyday that becomes the original raw material in the representation of modern man. Therefore, the family is an active category, present in the historicity of Nelson Rodrigues' thinking, skilled in portraying Rio's sociability in the northern zone. Imbued with a creative imagination and sensitive to the real, in this process, the city is seen as a panorama of transformation of the individuals who inhabit it, embodying different social practices. Due to this bias, the perception of several cities within one, feeds all the writer's ability to recreate his social types through fictional optics, permeated by the rhythms of urban experiences, revealing the heterogeneity of his narrative. Through a methodology of analysis of his theatrical and journalistic works, he seeks to perceive the social intimacy of a writer who, in view of the time of his experience, seeks to situate his critical conception of what it is to be feeling the historical transformations of his time, in a eternal romantic view of life. Keywords: Family. Moral. Theater. Practices. Daily.